Recife Frio: the Anthropocene in the light of a contemporary Brazilian film - Murari, Lucas (Farol, 2024)
This article aims to analyze the Brazilian film “Recife Frio”, by Kleber Mendonça Filho, from the perspective of climate change and its socio-environmental implications. Structured as a fake documentary, the short film inverts the temperature of Recife, provoking radical transformations in the sociability of the local population. Through a narrative that blends satire and reflection, the film addresses issues pertinent to the Anthropocene, such as the ecological crisis and environmental apartheid, highlighting the inequalities accentuated by climate change.
Keywords: Recife Frio; anthropocene; brazilian cinema; ecological crisis